DPP4-INHIBITOR LINAGLIPTIN ACCELERATES RESOLUTION OF CRESCENT FORMATION IN A RAT MODEL OF ANTI-GBM GLOMERULONEPHRITIS - Mayer, Anna-Lena; Ebert, Nadja; Klein, Thomas; Amann, Kerstin Ute; Daniel, Christoph (NEPHROLOGY DIALYSIS TRANSPLANTATION, 2020)
CRIS-Team WoS Importer:2020-08-21

Experimental renal transplantation in rats improves cardiac dysfunction caused by chronic kidney disease while LVH persists - Hagmayer, Linda; Mayer, Christina; Ebert, Nadja; Amann, Kerstin Ute; Daniel, Christoph (Frontiers in Cardiovascular Medicine, 2023)
Background: Chronic kidney disease (CKD) causes congestive heart failure (CHF) with systolic dysfunction and left ventricular hypertrophy (LVH), which is a major contributor to increased mortality in CKD patients. It remains unclear whether cardiovascular changes that occur during the course of CKD can be reversed when renal function is restored by transplantation. Methods: To investigate this, chronic kidney disease was established in F344 rats by subtotal nephrectomy (SNx) for 8 weeks, followed by transplantation of a functional kidney from an isogenic F344 donor. SNx rats without transplantation and sham-operated animals served as controls. Renal function was assessed before and throughout the experiment. In addition, cardiac ultrasound was performed at weeks 0, 8, 12 and 16. At the end of the experiment, intra-arterial blood pressure was measured and kidneys and hearts were histologically and molecularly examined. Results: Eight weeks after SNx, rats developed marked renal dysfunction associated with significant glomerulosclerosis and tubulointerstitial fibrosis, but also an increase in left ventricular mass. After transplantation, renal function normalized but relative heart weight and ventricular mass as assessed by ultrasound scans showed no reduction compared with SNx controls. However, left ventricular wall thickness, fractional shortening and ejection fraction was normalized by renal transplantation. At 8 weeks after kidney transplantation, cardiac expression of BNP and FGF23 was also at levels comparable to healthy controls, whereas these factors were significantly increased in SNx rats. Cardiac fibrosis, as measured by fibronectin mRNA expression, was completely normalized, whereas cardiac fibronectin protein was still slightly but not significantly increased in transplanted animals compared to controls. In addition, the myofibroblast marker collagen 1, as assessed by immunohistochemistry, was significantly increased in SNx rats and also normalized by renal transplantation. Interestingly, CD68+ macrophages were significantly reduced in the hearts of SNx rats and in transplanted animals at slightly higher levels compared to controls. Conclusion: Restoration of renal function by kidney transplantation normalized early cardiac changes at most functional and molecular levels, but did not completely reverse LVH. However, further studies are needed to determine whether restoration of renal function can also reverse LVH at a later time point.
CRIS-Team Scopus Importer:2023-08-11
Keywords: cardiac hypertrophy; chronic kidney disease; FGF23; fibrosis; renal tranplantation

Is Early Complement Activation in Renal Transplantation Associated with Later Graft Outcome? - Bobka, Steffen; Ebert, Nadja; Koertvely, Eloed; Jacobi, Johannes; Wiesener, Michael; Büttner-Herold, Maike; Amann, Kerstin Ute; Daniel, Christoph (Kidney & Blood Pressure Research, 2018)
BACKGROUND/AIMS: Complement activation is important in post-transplantation renal injury, but data on its role as predictor of transplant outcome/complications when assessed in donor kidneys are lacking. METHODS: In human renal transplant biopsies with delayed graft function (DGF, n=12), antibody mediated rejection (ABMR, n=8), T-cell mediated rejection (TCMR, n=11), 1 year protocol biopsies (control, n=10) and corresponding zero-biopsies we performed immunohistochemical analyses of 6 complement factors using FFPE sections and correlated the findings with kidney function, as assessed by serum creatinine, and morphological changes including interstitial fibrosis and tubular atrophy (IF/TA). RESULTS: In DGF, TCMR and ABMR significant complement deposition was observed, which was less pronounced in corresponding zero-biopsies. Zero-biopsies with subsequent ABMR showed glomerular complement factor D and C3c expression. Moreover, glomerular C3c and C9 and tubular MASP-2 and Collectin-11 expression in zero-biopsies significantly correlated with serum creatinine at diagnosis of DGF, TCMR or ABMR. Glomerular C1q was significantly increased in ABMR, but not in DGF and TCMR. In contrast, peritubular C1q was significantly enhanced in DGF and TCMR compared to zero-biopsies. Using C3d as a surrogate marker for complement activity we could confirm that stained complement factors are frequently associated with complement activity. CONCLUSION: Complement deposition strongly correlated with histopathological changes observed in renal transplants. All 3 complement pathways were operational in biopsies with DGF, TCMR and ABMR albeit with differential abundance and localization. Since complement deposition in zero-biopsies correlated with graft function and morphological changes, early specific complement inhibition in renal transplantation may be a new therapeutic option to prevent graft loss.
EVALuna2:35394

Serum Uromodulin as early marker for ischemic acute kidney injury and nephron loss: association with kidney tissue distribution pattern - Vonbrunn, Eva; Ebert, Nadja; Cordasic, Nada; Amann, Kerstin Ute; Büttner, Anke; Büttner-Herold, Maike; Scherberich, Jürgen E.; Daniel, Christoph (Journal of Translational Medicine, 2025)
Background: Uromodulin (UMOD) is expressed in kidneys and is mainly excreted in the urine, although a smaller amount is also released into the serum. Here, we investigated UMOD in acute kidney injury (AKI), with particular focus on the utility of serum UMOD as marker for nephron loss. Methods: Blood and kidney samples were collected 6 h, 24 h, 3 days and 8 weeks after ischemia/reperfusion (I/R) in a rat model. To investigate the impact of nephron number on UMOD levels, sera and tissue from healthy, uninephrectomized (Unx) and 5/6-nephrectomized (Snx) rats were analyzed. Histological changes, kidney function and cell damage were evaluated and serum UMOD, Umod mRNA expression and distribution of UMOD protein in the kidney were examined. Results: In AKI, kidney function was markedly impaired 24 h after I/R, while kidney injury and serum UMOD was increased transiently. Simultaneously, the amount of UMOD-positive kidney cells rapidly decreased 24 h after I/R compared to healthy kidneys, and mRNA expression of Umod was lowest on days 1–3 after I/R. Serum UMOD correlated with nephron number showing the highest levels in healthy rats, which were reduced after Unx and further reduced after Snx. Conclusion: In an AKI model with severe tubular damage, a transient increase in UMOD serum levels in parallel with loss of UMOD-positive cells suggests temporary release of UMOD from destroyed tubular cells into the blood. Serum UMOD appears to be not only a marker of chronic renal failure but also of acute loss of functional and cellular integrity of kidney epithelia in AKI.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Acute kidney injury; Ischemia/reperfusion; Nephron loss; Tamm-Horsfall protein; Uromodulin

The dipeptidyl peptidase 4 inhibitor linagliptin ameliorates renal injury and accelerated resolution in a rat model of crescentic nephritis - Mayer, Anna-Lena; Scheitacker, Iris; Ebert, Nadja; Klein, Thomas; Amann, Kerstin Ute; Daniel, Christoph (British Journal of Pharmacology, 2021)
Background and Purpose: Dipeptidyl peptidase 4 (DPP-4) inhibitors are a class of oral glucose-lowering drugs used in the treatment of type 2 diabetes. In a pilot study using human kidney biopsies, we observed high DPP-4 expression in early crescent formation. This glomerular lesion occurs in different kidney diseases and is a hallmark in the pathogenesis of renal dysfunction. Therefore, we investigated the potential involvement of DPP-4 in the pathogenesis of nephritis induced by anti-glomerular basement membrane (GBM) antibody in rats. Experimental Approach: Linagliptin and vehicle were used to treat anti-GBM nephritis in a 2- and 8-week regimen, that is either preventive or therapeutic (treatment started 7 days or 4 weeks after disease induction). Kidney function, morphologic changes, inflammation and fibrosis were monitored. Key Results: In the long-term experiment, linagliptin preventive treatment in anti-GBM nephritic rats significantly reduced the number of crescents, glomerulosclerosis, tubular injury and renal fibrosis, compared with those in untreated nephritic rats. Both linagliptin regimes significantly lowered the number of Pax8+ cells on the glomerular tuft in anti-GBM nephritis, indicating accelerated resolution of the cellular crescents. The linagliptin treatment did not change the podocyte stress in both therapeutic groups. Therapeutic intervention with linagliptin resulted in weaker amelioration of renal disease on Week 8 than did preventive intervention. Conclusion and Implications: DPP-4 inhibition with linagliptin ameliorates renal injury in a rat model of anti-GBM, indicating that linagliptin not only is a secure therapy in diabetes but also can improve resolution of glomerular injury and healing in non-diabetic renal disease.
CRIS-Team Scopus Importer:2021-02-12
Keywords: crescent formation; DPP-4 inhibitor; fibrosis; non-diabetic renal disease

The new semisynthetic cardenolide analog 3β-[2-(1-amantadine)-1-on-ethylamine]-digitoxigenin (AMANTADIG) efficiently suppresses cell growth in human leukemia and urologic tumor cell lines - Nolte, Elke; Sobel, Anna; Wach, Sven; Hertlein, Heidi; Ebert, Nadja; Müller-Uri, Frieder; Slany, Robert; Taubert, Helge; Wullich, Bernd; Kreis, Wolfgang (Anticancer Research, 2015)
Background/Aim: The use of cardenolides in the treatment of cardiac insufficiency is well-established. However, the potential of cardenolides in tumor therapy has not been comprehensively studied. The aim of the present study was to characterize the cytotoxic effects of the new semisynthetic cardenolide analog AMANTADIG (3β-[2-(1-amantadine)-1- on-ethylamine]-digitoxigenin), and the cardenolide digitoxin on leukemia and urological tumor cell lines. Materials and Methods: The anti-proliferative effects of AMANTADIG and digitoxin on leukemia and urological cancer cell lines were analyzed using (3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) tetrazolium reduction viability assay. Results: AMANTADIG and digitoxin exhibited antiproliferative activities against the leukemia cell lines in the low nanomolar range. The prostate cancer and renal cell carcinoma cell lines were equally sensitive to AMANTADIG and digitoxin, however, the leukemia cell lines were more sensitive to both cardenolides. Conclusion: The new cardenolide analog AMANTADIG appears effective in cell growth inhibition of leukemia and urological tumor cell lines.
Keywords: 3β-[2-(1-Amantadine)-1-on-ethylamine]-digitoxigenin; AMANTADIG; Cardenolide analog; Human leukemia cells; Human urological cancer cells; Porcine cerebral cortex Na+/K+-ATPase